1975
DOI: 10.1021/jf60200a031
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, excretion, and metabolism of methoprene by a guinea pig, a steer, and a cow

Abstract: This paper reflects the results of research only. Mention of a pesticide or a proprietary product in this paper does not constitute a recommendation or an endorsement of this product by the U.S. Department of Agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…et al, 1975b) have shown that it is nonpersistent and rapidly degraded. Some animal metabolism studies have been performed in the guinea pig, steer, and cow (Quistad et al, 1975b,c;Chamberlain et al, 1975) and complementary to these investigations we now report the fate of methoprene in rats.…”
mentioning
confidence: 66%
“…et al, 1975b) have shown that it is nonpersistent and rapidly degraded. Some animal metabolism studies have been performed in the guinea pig, steer, and cow (Quistad et al, 1975b,c;Chamberlain et al, 1975) and complementary to these investigations we now report the fate of methoprene in rats.…”
mentioning
confidence: 66%
“…When methoprene-5-14C was given to cattle, demethylated and deisopropylated metabolites of methoprene were identified in feces and urine (Chamberlain et al, 1975), but radioactivity was associated with milk fat, lactose, lactalbumin, and casein (Quistad et al, 1975c). Methoprene can be partly metabolized to acetic acid by cattle (Quistad et al, 1974), and some of this acetic acid may be used for synthesis of cholesterol (Quistad et al, 1975a).…”
Section: Resultsmentioning
confidence: 99%
“…When a lactating Jersey cow was given a large single dose of [5-14C]methoprene (1), 8% of the radioactivity appeared in milk (Chamberlain et al, 1975). The chemical nature of the constituent radioactivity in milk was examined in order to analyze for possible presence of 1 and/or its primary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…We now report the chemical identity of the degradation products resulting from the metabolism of 1 by a lactating dairy cow. A radioactivity balance study will be reported for the same cow (Chamberlain et al, 1975). This work is part of a comprehensive investigation of the environmental degradation of methoprene (for part VII, see Quistad et al, 1975).…”
mentioning
confidence: 99%